UTILIZATION HARVEST WASTE AS ORGANIC FERTILIZER BY COMPOSTING ON PADDY FARMER GROUP AT HUTAGAOL PEATALUN VILLAGE, BALIGE KABUPATEN TOBA SAMOSIR - Dermawan Hutagaol; Aisyah Lubis; Nurma Ani (AGRIUM: Jurnal Ilmu Pertanian, 2016)
Paddy sawah cultivation that done for long time used chemical fertilizer with dosage that continously increased  but many reports indicated no  respond on increasing paddy production. Utilization of chemical fertilizer caused decreased soil quality, which  fertilizer respond  was less that indicated  by  production that hard to increase while  fertilizer dosage  was  increased every year so farm cost more expensive especially for buy fertilizer. This problem must be solved by applicated res earch result for farmer with utilized harvest waste as organic fertilizer by composting. This IbM activity aim was to used  harvest waste as organic fertilizer by composting to decrease fertilizer cost and  farmer income be increased. This activity target was found IPTEKS for farmer how processes to made harvest waste be organic fertilizer by composting to increased fertilizer efficiency so  that chemical fertilizer can decreased. This activity result after socialized about utilization and  composting processes was farmer understood and could made compost from harvest waste and  increased  farmer knowledge abaout utilization harvest waste as organic fertilizer.Key words: compost, farmer, harvest waste